PERANCANGAN DAN PENGEMBANGAN PRODUK RAGUM DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Robertus Sidhartawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2012)
Vise used in the work bench or work processes functioning manual for gripping the workpiece and can also be used in the machining process. Most of the manufacturing industry in Indonesia, still not able to design their own products. In the process of making problems often arise include the design can not be realized, the high cost of manufacture or product functionality that is not being met, so it can be said that not enough manufacturing industries are well qualified to produce quality products that can compete. Quality Function Deployment (QFD) is a method used to anticipate and prioritize the needs and desires of consumers, as well as incorporating the needs and desires of the consumer goods and services produced by the company. The purpose of this research is to design and develop products vise using the Quality Function Deployment. The data required in this study consisted of primary data and secondary data. Primary data were obtained from the distribution of questionnaires to the respondents. Secondary data was collected through library research. From the research, it can develop new products with specifications vise: (1) vise must be equipped with a third axis of rotation (14.14%), (2) vise with solid physical form (10.71%), (3) Price selling cheap (10.20%), (4) is equipped with a vise grip (9.05%), (5) vise is equipped with a practical guide (9.04%), (6) vise should be light (9, 03%), (7) pencekam jaw vise flexible, flat (8.27%), (8) vise easy to diasembling (8.27%), (9) Material of vise HR 1040 (7.6%), (10) Age used (7.36%), (11) The components easily obtainable (6.36%). Key word : Vise, Quality Function Deployment, House of Quality